1998
DOI: 10.1172/jci1649
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase inhibits high-density lipoprotein oxidation and preserves its functions. A possible peroxidative role for paraoxonase.

Abstract: HDL levels are inversely related to the risk of developing atherosclerosis. In serum, paraoxonase (PON) is associated with HDL, and was shown to inhibit LDL oxidation. Whether PON also protects HDL from oxidation is unknown, and was determined in the present study. In humans, we found serum HDL PON activity and HDL susceptibility to oxidation to be inversely correlated ( r 2 ϭ 0.77, n ϭ 15). Supplementing human HDL with purified PON inhibited copper-induced HDL oxidation in a concentrationdependent manner. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
769
1
24

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,053 publications
(827 citation statements)
references
References 56 publications
33
769
1
24
Order By: Relevance
“…In the past few decades, it has become evident that high density lipoprotein (HDL) has antioxidant properties that protect LDL and HDL particles from oxidation. During this process, the HDLassociated enzyme paraoxonase1 (PON1) has been suggested as a possible mechanistic cause of this phenomenon [3,28,29,33,49]. PON1 belongs to the paraoxonase (PON) gene family which is located on chromosome 7q21.3-22.1 [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, it has become evident that high density lipoprotein (HDL) has antioxidant properties that protect LDL and HDL particles from oxidation. During this process, the HDLassociated enzyme paraoxonase1 (PON1) has been suggested as a possible mechanistic cause of this phenomenon [3,28,29,33,49]. PON1 belongs to the paraoxonase (PON) gene family which is located on chromosome 7q21.3-22.1 [37].…”
Section: Introductionmentioning
confidence: 99%
“…PON1 has protective action against atherosclerosis in both in vitro and in vivo models. Indeed, PON1 protects LDL particles against copper-induced lipid oxidation in vitro [3,28,29] and transgenic mice overexpressing the human PON1 gene have reduced atherosclerotic lesions [48]. Moreover, PON1 knockout mice display accelerated atherosclerosis progression and increased lipid oxidation [40,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that PON1 associates with high-density lipoprotein (HDL) [1] and inhibits the oxidation of low-density lipoprotein (LDL) and HDL [2,3]. PON1 knockout mice were unable to protect against the progression of atherosclerosis by feeding on a high fat and high cholesterol diet [4], and atherosclerotic lesion formation was decreased in PON1 transgenic mice [5].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies will focus on genes like Bcl2l10 or C/EBP which were up-regulated during hypoxia and which are known to be anti-apoptotic (Song et al 1999;Naumann et al 2001;Buck and Chojkier 2003). Additionally, strongly up-regulated genes (not shown) like Paraoxonase 1, which is involved in oxidative stress response and lipid oxidation (Aviram et al 1998) or Adrenomedullin, which was reported to be neuroprotective in ischemia models (Miyashita et al 2006) will be studied for their relevance to retinal neuroprotection after hypoxic preconditioning.…”
Section: Discussionmentioning
confidence: 99%